The ostensible originality of ungrading - Dhillon, Sunny (Educational philosophy and theory, 2025)
This article contributes to the emerging literature about ungrading within Higher Education across disciplines in the anglosphere. The piece offers a critical take on the apparent originality of ungrading practices. Such practices appear on a spectrum, from minor adjustments to summative grades by alternating the numerical with the alphabetized form or vice versa, to replacing grades on a module via oral and/or written feedback. Whilst ungrading may prima facie appear original, contrary to the claims of many of its contemporary proponents, this critical discussion argues that it does not involve sufficient reflection upon the telic aims of the university apparatus; namely, in the awarding of a classified degree or Grade Point Average, nor upon the implicated role of the educator, in a manner befitting genuinely transgressive practice. To supplement the growing research on ungrading, this article argues that adopting game theory may help sharpen future ungrading practices to be more critically reflective, and perhaps original.